Roxio Easy media creator 8 in a snap - Dayley, Lisa DaNae (Sams teach yourself., 2006)
Spend less of your valuable time reading and more time doing! Roxio Easy Media Creator in a Snap is designed specifically for today's busy digital media enthusiast like you. Organized into a series of well-organized, bite-sized, quickly accomplished tasks, this book lets you zero right in on the one particular task you want to accomplish, quickly figure out what to do, do it, and then get back to work. You'll find out how to organize, edit, and share digital photos, video, and audio. Roxio Easy Media Creator in a Snap also provides you with the answers you will need to get started burning discs; edit various media formats; organize and share photo video, and music collections; design creative slideshows, video productions, and DVDs; and archive and back up your precious memories.